Targeted Sequencing and RNA Assay Reveal a Noncanonical JAG1 Splicing Variant Causing Alagille Syndrome - Chen, Yiyao; Liu, Xueli; Chen, Songchang; Zhang, Junyu; Xu, Chenming (Frontiers in Genetics, 2020)
Alagille syndrome (ALGS), as known as congenital arteriohepatic dysplasia, is a rare autosomal dominant multi-systemic disorder. Mutations in JAG1 or more rarely NOTCH2 have been reported as the cause of ALGS. In this study, a 5-year old girl with typical ALGS feature and her pregnant mother came to our reproductive genetics clinic for counseling. We aimed to clarify the genetic diagnosis and provide prenatal genetic diagnosis for the pregnant. Next generation sequencing (NGS)-based multigene panel was used to identify pathogenic variant of the proband. Then the candidate variant was verified by using Sanger sequencing. RNA assay was performed to clarify splicing effect of the candidate variant. Amniocentesis, karyotyping, and Sanger sequencing were performed for prenatal testing. We found a novel de novo noncanonical JAG1 splicing variant (c.2917-8C>A) in the proband. Peripheral blood RNA assay suggested that the mutant transcript might escape nonsense-mediated mRNA decay (NMD) and encode a C-terminal truncated protein. Information of the variant has resulted in a successful prenatal diagnosis of the fetus. Our results clarified the genetic diagnosis of an ALGS patient and ensured utility of prenatal genetic testing.